The Model of Odonate Diversity Relationship with Environmental Factors Based on Path Analysis - Feriwibisono, Bambang; Marsoedi, Marsoedi; Leksono, Amin Setyo (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2016)
This study aims to analyze and describe the relationship between altitude, aerial variables (temperature, light intensity, humidity), water qualities (water temperature, pH, BOD, COD, DO, TOM, and water velocity), and vegetation with the diversity of Odonate assemblages. Odonate samplings were conducted at six survey sites based on altitude and vegetation characteristics. Measurement of altitude, aerial variables, water qualities and vegetation characteristics were replicate in the first day and third day. Analysis of correlations of all environmental factors with the odonate diversity was done through structural equation model using Partial Least Squares (PLS), Open source Smart Software and Microsoft Excel. The aerial variables and water qualities affected indirectly on odonate diversity. The aerial variables directly or with interaction to other factor affected the water qualities and vegetation characteristics. The vegetation characteristics directly influenced to odonate diversity. Water flow affected water quality, light intensity affected the aerial, while morning period observation affected the odonate diversity. Predictive relevance (Q2) for a model designed amounted to 99.95%, while the rest of 0.05% are explained by other variables.Â